PENGARUH KUALITAS PELAYANAN DAN LOKASI TERHADAP KEPUASAN PELANGGAN KEDAI SAMBAL BAKAR RAI RAKA DI BANDUNG - Sultan Raafly Rama Putra; Ani Surtiani (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to analyze the effect of service quality and location on customer satisfaction at Kedai Sambal Bakar Rai Raka in Bandung. The study uses a quantitative approach with an associative method. The study population is all customers of Kedai Sambal Bakar Rai Raka with an accidental sampling technique of 93 respondents. Data collection was conducted through questionnaires, while data analysis used multiple linear regression with the help of the SPSS program. The results of the study indicate that service quality and location have a positive and significant effect on customer satisfaction.